The poly(A) polymerase beta gene may not be associated with azoospermia caused by Sertoli-cell-only syndrome in Japanese patients by comparing patients and normal controls. (3rd April 2019) - Miyamoto, T.; Shin, T.; Iijima, M.; Minase, G.; Okada, H.; Saijo, Y.; Sengoku, K.
Abstract: Approximately 15% of couples are infertile, with half of these cases being due to a male factor. Testis-specific cytoplasmic poly(A) polymerase beta (PAPOLB) is known to be critical for spermatogenesis. In mice, the loss of function of the Papolb gene results in the arrest of spermiogenesis and in male infertility. To analyse the role of the PAPOLB gene in human male infertility, this study investigated the relevance of this gene to human Sertoli-cell-only syndrome (SCOS) with azoospermia. Mutation analysis of the PAPOLB coding region was performed on 139 Japanese patients by PCR and direct sequence analysis. No critical mutations directly causing SCOS were detected, but three single-nucleotide polymorphisms (SNPs; SNP1 (c1101C > T), SNP2 (c1347T > C) and SNP3 (c1903C > A)) were found in the coding region. However, there were no significant associations in the allelic and genotypic distributions of these three SNPs between the SCOS and control groups ( p >.05). This study suggests a lack of association of PAPOLB with azoospermia due to SCOS in humans.